Influencia de las técnicas lúdicas en el proceso de enseñanza- aprendizaje en el área de Matemática de los niños del Tercer Grado de Educación General Básica de la Unidad Educativa "Digna Beatriz Cerda Neto", del Cantón Pujilí en el periodo lectivo 2016-2017. - Guishca Ayala, Loide Adriana (2018)
The objective of this investigative project was to diagnose ludic techniques focused on education and improving the teaching/learning process in the area of mathematics for children of the third grade of basic general education, in the Educational Unit "Digna Beatriz Cerda Neto", located in Pujilí canton. The use of playful techniques in education is a strategy that allows acquiring knowledge in a practical and fun way for students in order to develop their logical mathematical thinking during the teaching/learning process. For the execution of this project, three types of research were used, which allowed us to reach an analysis of the object of study and these are: field, bibliographic and exploratory research. The sample of the study consisted of twenty-nine boys, seventeen girls and two teachers of the Educational Unit "Digna Beatriz Cerda Neto". Survey and interview were used as a technique, and observation guide, as an instrument: a questionnaire composed of seven items for students and ten for teachers. As a result of this investigation, it was possible to know that the use of the playful techniques is little applied by the teachers to develop activities in the area of mathematics. To contribute and improve the teaching/learning process of mathematics, a manual of playful techniques was elaborated that contemplates diverse activities that can lead to a better motivation of the students for learning mathematics. In conclusion, it was the best strategy that gave us optimal results which through mathematical games can achieve any goal that is intended during the class; It also recognized the need to incorporate play techniques as a resource and didactic strategy to contribute to the teaching of mathematics.